Variables Associated With Return to Sport Following Anterior Cruciate Ligament Reconstruction: A Systematic Review - Czuppon, Sylvia (2013)
BACKGROUND: As one of the purposes of anterior cruciate ligament reconstruction (ACLR) is to return athletes to their pre-injury activity level, it is critical to understand variables influencing return to sport. Associations between return to sport and variables representing knee impairment, function and psychological status have not been well studied in athletes following ACLR. PURPOSE: The purpose of this review is to summarize the literature reporting on variables proposed to be associated with return to sport following anterior cruciate ligament reconstruction. STUDY DESIGN: Systematic Review METHODS: Medline, Embase, CINAHL and Cochrane databases were searched for articles published before November 2012. Articles included in this review met these criteria: 1) included patients with primary ACLR, 2) reported at least one knee impairment, function or psychological measure, 3) reported a return to sport measure and 4) analyzed the relationship between the measure and return to sport. RESULTS: Weak evidence existed in sixteen articles suggesting variables associated with return to sport included higher quadriceps strength, less effusion, less pain, greater tibial rotation, higher Marx Activity score, higher athletic confidence, higher pre-operative knee self-efficacy, lower kinesiophobia and higher pre-operative self-motivation. CONCLUSION: Weak evidence supports an association between knee impairment, functional, and psychological variables and return to sport. Current return to sport guidelines should be updated to reflect all variables associated with return to sport. Utilizing evidence-based return to sport guidelines following ACLR may ensure athletes are physically and psychologically capable of sports participation, which may reduce re-injury rates and the need for subsequent surgery.